Feasibility of nephron sparing surgery in giant oncocytoma - El Hajj, Albert; Thanigasalam, Ruban; Boulay, Isabelle; Molinié, Vincent; Escudier, Bernard; Baumert, Hervé (Canadian Urological Association Journal, 2014)
Oncocytomas represent 3 to 7% of renal masses and behave as benign tumours. Nephron-sparing procedures are preferred for biopsy confirmed lesions; however, giant oncocytomas have been generally treated by radical nephrectomy. We report the first case of partial nephrectomy in a 45-year-old man who presented with a 20-cm oncocytoma. At the 1 year follow-up, he had a normal functioning kidney. Despite the difficulty of this procedure, partial nephrectomy for very large benign tumours can be considered in appropriately selected young patients.